Evaluasi Persediaan Obat Dengan Floor Stock Berdasarkan STARKES 2022 Pada Unit Farmasi Rawat Inap RSPGD - Khikam, Ulil Abshor Al; Santoso, Rahmat Agus; Khoerunnisa, Tiara; Saepulloh, Asep (Universitas Muhammadiyah Gresik, 2023)
Background – The Inpatient Ward is one of the most crucial parts of hospital operations, reflecting a commitment to providing intensive care to patients. Objective – This study aims to describe the fulfillment of the Floor Stock drug distribution system standards in the Inpatient Unit of RS Petrokimia Gresik Driyorejo based on STARKES 2022. Design / Methodology / Approach – This research uses a qualitative descriptive research method with a case study design. Data collection is carried out through observation, in-depth interviews, and documentation. Findings – Observations were carried out using the STARKES 2022 accreditation standard checklist before implementation of the treatment. Based on observations using the STARKES 2022 accreditation standard checklist before the intervention was carried out, a result of 36% was obtained. Research Implication – This study is expected to be a concrete step towards improvement and enhancement in supporting the smooth operation of inpatient services at Petrokimia Gresik Hospital, Driyorejo. Limitations – The research object is limited to drug storage only and not as a whole, including other Pharmaceutical Preparations, Medical Devices, and Disposable Medical Materials.